(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article highlights the influence that nations exert on each other through diplomatic and creative activities through various contacts. This inherent historical premise will always be relevant in the lives of peoples. The authors who wrote the work put the question on this line. And the purpose of the study is to show that this is a value that gives strength, uniqueness, contribution to the development of poetry, examples of love for the motherland, its protection, which both give and strengthen the spiritual connection between peoples. The research method is associated with the use of poetic material – the most beautiful of the spiritual riches of mankind, close to the heart. We have chosen a method of studying the lyrical, patriotic, family texts of female poets of Chinese civilization. When society develops, civilization flourishes, spiritual resources serve humanity, preserve life, purify it. Poetry is also deeply rooted in the hearts of the Chinese people, not remaining unchanged and being updated along with the general development. The topic of our article is innovation in poems created by female poets in Chinese poetry.